Multilayer Thin Films Versatile Applications for Materials Engineering - Basu, Sukumar (IntechOpen, 2020)
This book, "Multilayer Thin Films-Versatile Applications for Materials Engineering", includes thirteen chapters related to the preparations, characterizations, and applications in the modern research of materials engineering. The evaluation of nanomaterials in the form of different shapes, sizes, and volumes needed for utilization in different kinds of gadgets and devices. Since the recently developed two-dimensional carbon materials are proving to be immensely important for new configurations in the miniature scale in the modern technology, it is imperative to innovate various atomic and molecular arrangements for the modifications of structural properties. Of late, graphene and graphene-related derivatives have been proven as the most versatile two-dimensional nanomaterials with superb mechanical, electrical, electronic, optical, and magnetic properties. To understand the in-depth technology, an effort has been made to explain the basics of nano dimensional materials. The importance of nano particles in various aspects of nano technology is clearly indicated. There is more than one chapter describing the use of nanomaterials as sensors. In this volume, an effort has been made to clarify the use of such materials from non-conductor to highly conducting species. It is expected that this book will be useful to the postgraduate and research students as this is a multidisciplinary subject.